An Efficient One-Pot Synthesis of Condensed Imidazoles Using Pentafluorophenylammonium Triflate as Novel, Metal-free and Reusable Catalyst - Montazeri, Naser; Esmaeili, Abbas (Asian Journal of Chemistry, 2013)
A superior method of synthesis of condensed imidazoles by the catalytic action of pentafluorophenylammonium triflate on the reaction of 1,2-diaminoaromatics with orthoesters is described. The catalyst is reusable and can be applied several times without considerable decrease in the yields and rates of the reaction.